Thermally enhanced slip casting of alumina ceramics - A.M. Murfin; J.G.P. Binner (1998)
Slip casting is a process which is very suitable for the production of large components and thin-walled bodies of complex shape but which is also time and energy intensive. One method of increasing the casting rate is by heating the slip. This has been examined via the use of both microwave and convectional heat energy for 72wt% nitric acid dispersed aqueous alumina slips. It has been found to provide an increase in the casting rate over ambient temperature processing, with a gain of 55% when using microwave energy and 20% using a convection oven at 45degreesC. The enhanced rate is apparently achieved via two mechanisms. At temperatures less than approximately 40degreesC it is probably due to a reduction in the slip viscosity enabling easier water movement through the cast layer and mould. At higher temperatures there is a change in the dispersion state of the slip. It appears that as the slip temperature increases above ambient the slip becomes increasingly flocculated and that above about 45degreesC this influences the casting rate. By 65degreesC the slip is fully flocculated. A further enhancement in the casting rate is achieved with microwave energy over convectional heat energy. This is attributed to the rate of movement of water through the mould being increased more than the rate of water uptake by the mould. This in turn is believed to be due to the plaster of paris being essentially transparent to microwave radiation so that the only significant heating that occurs in the mould is due to the presence of the water. Since the water in the mould cannot move around as freely as it can in the slip, local temperature gradients can rapidly develop. This causes the water front within the mould to move faster than with convectional heating. No evi- dence has been found that this accelerated rate has any detrimental effect on the cast body produced.